Practice-based Education : Enhancing Practice and Pedagogy : Final Fellowship Report. - Higgs, Joy (Australian Learning and Teaching Council (ALTC), 2011)
Final report of a Teaching Fellowship at Charles Sturt University. This research explored Practice-Based Education (PBE) in universities which is an approach to education that is grounded in the preparation of graduates for occupational practice. The Fellowship program examined, developed and disseminated good practices and pedagogies in PBE. Over 300 participants from over 20 institutions in Australia and overseas engaged in the critique and dissemination in order to embed the findings in higher education. In addition, over 100 publications and over 50 conference presentations involving over 300 authors and presenters arose from Fellowship generated activities. Good practices from individuals, courses and institutions were profiled across multiple institutions in Australia and overseas. These networking and dissemination activities operated at multiple levels and sites of the collaborative inquiries that comprised the Fellowship program. The impact and potential for future developments arising from this fellowship program are far reaching. This report documents these activities and their outcomes/ products. A model of PBE Pedagogy is presented.